Design methods for steel fiber reinforced concrete industrial floors - Barros, Joaquim A. O. (2005)
Industrial floors are still the main application of steel fiber reinforced concrete (SFRC). Crack control joints are made to concentrate the crack propagation in these weakness-induced surfaces, resulting in a floor divided in panels. The design of a SFRC floor is currently made by means of the study of one of these panels, using the yield line method (YLM). The ultimate load of the panel depends on the maximum bending moment of the slab. Since in flooring applications the content of steel fibers, in general, does not exceed 45 kg/m3, the maximum bending moment is only slightly increased by the presence of steel fibers. Therefore, when the YLM is used to design this type of SFRC application the contribution of the fiber reinforcement cannot be accurately simulated. In the present work, this deficiency of the YLM is shown and justified by means of experimental and numerical research. Furthermore, the YLM is unable to predict the force-deflection relationship of a concrete slab supported on soil. The finite element method (FEM) is a powerful tool to analyze this type of structures. However, the accuracy of the analysis depends on the quality of the constitutive model used to simulate the nonlinear behavior of the intervening materials. For this purpose, an appropriate constitutive model was developed and is briefly described in the present work. This model is used in the analysis of SFRC slabs on soil. Using experimental results and applying the corresponding computational code, a numerical strategy for establishing design charts for SFRC slabs on soil is proposed.